Ecological-economic viability as a criterion of strong sustainability under uncertainty - Stefan Baumgärtner; Martin F. Quaas (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
Strong sustainability, according to the common definition, requires that different natural and economic capital stocks have to be maintained as physical quantities separately. Yet, in a world of uncertainty this cannot be guaranteed. To therefore define strong sustainability under uncertainty in an operational manner, we propose to use the concept of viability. Viability means that the different components and functions of a dynamic, stochastic system at any time remain in a domain where ...
Keywords: D81; Q01; Q57; 330; Nachhaltige Entwicklung; Definition; Risiko; Weidewirtschaft; Theorie